2020
DOI: 10.35489/bsg-rise-ri_2020/021
|View full text |Cite
|
Sign up to set email alerts
|

Building on Solid Foundations: Prioritising Universal, Early, Conceptual and Procedural Mastery of Foundational Skills

Abstract: In 1990, the global community, gathered for the World Conference on Education for All in Jomtien, Thailand, declared that all children should be provided a quality education to "meet their basic learning needs" (World Declaration on Education for All, 1990). This focus on learning was amplified by the adoption of the Sustainable Development Goals (SDG) in 2015, which include a target to provide every child with an education that leads to relevant and effective learning by 2030 (SDG 4.1). Despite these commitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Progress in the earlier years of school shapes later outcomes: the less a child learns in the early years of school, the less that child tends to learn in the later years. This makes sense because learning is a cumulative process where foundational skills are the scaffolding needed to learn higher-order skills (Belafi, Hwa, and Kaffenberger 2020). Said intuitively, children need to be able to read letters before words, and to read words before they can understand paragraphs.…”
Section: Systems Must Increase Learning Per Year Beginning In the Ear...mentioning
confidence: 99%
See 2 more Smart Citations
“…Progress in the earlier years of school shapes later outcomes: the less a child learns in the early years of school, the less that child tends to learn in the later years. This makes sense because learning is a cumulative process where foundational skills are the scaffolding needed to learn higher-order skills (Belafi, Hwa, and Kaffenberger 2020). Said intuitively, children need to be able to read letters before words, and to read words before they can understand paragraphs.…”
Section: Systems Must Increase Learning Per Year Beginning In the Ear...mentioning
confidence: 99%
“…In many countries curricula and instruction are overambitious relative to the actual quality of instruction, moving too fast for children to keep up (Pritchett and Beatty 2012;Kaffenberger and Pritchett 2020). When children do not master foundational skills like reading and mathematics in the early primary years, they are not able to engage in more advanced topics in later grades (Belafi et al 2020;Gordon et al 2019). In India, for example, a study that assessed children against grade-based standards found that many children in grades 7 and 8 were at only a grade 2 curricular level (Muralidharan 2019; Muralidharan and Singh forthcoming).…”
Section: Principles For Aligning Instruction For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…There are good reasons for countries to have an "early" education poverty standard (e.g. grades 2/3/4 or around age 10) for a minimal level of foundational learning, such as conceptual and procedural mastery of foundational skills (Belafi, Hwa and Kaffenberger, 2020). Many education systems are currently more "selection" systems than "education" systems (Muralidharan and Singh, 2021) and use late (grade 10 or 12), life-chance determining, highstakes for students, examinations to select which students are eligible for scarce preferred education and career opportunities.…”
Section: Target 41 By 2030 Ensure That All Girls and Boys Complete Fr...mentioning
confidence: 99%
“…An early global minimum standard of conceptual and procedural mastery of foundational skills will also help to "teach at the right level" (Belafi, Hwa, and Kaffenberger 2020, Banerjee et al 2016, Hwa, Kaffenberger, and Silberstein, 2020 and avoid the "negative consequences of overambitious curriculum" (Pritchett and Beatty 2012) and hence is instrumentally essential to achieving late learning standards. A minimum learning standard needs to encompass both conceptual and procedural mastery, not merely rote memorization of number facts or, as above, decoding skills.…”
Section: Target 41 By 2030 Ensure That All Girls and Boys Complete Fr...mentioning
confidence: 99%